1997
DOI: 10.1111/j.1600-0625.1997.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin changes in “screen dermatitis” versus classical UV‐ and ionizing irradiation‐related damage — similarities and differences

Abstract: Skin changes in ''screen dermatitis" versus classical UV-and ionizing irradiation-related damage -similarities and differences Two neiiroscieiitists' speculative review (jatigi S. .lohanssoti O. Skin cbatiges iti "screen dertnalilis" \orstts classical L'V-atui iotiizing irradialion-rclatcd damage -similarities and dilTcrences. Two tieuroscietilists' speculative rc\ie\v. Exp Dermalol 1997: 6: 28.^ 291. t^ Munksgaard. 1997 Abslracl: Ati increasing tnnnbcr of persotis sa\ thai llic\ gel cutaticous protilctns as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
(7 reference statements)
0
11
1
1
Order By: Relevance
“…A reasonable explanation for the lower wrinkling and spots would be a small but long-term difference in sun exposure, which may not have been accurately assessed by the survey used in this study. One study reported that Langerhans' cells were depleted in "screen dermatitis" (Gangi and Johansson 1997), but we did not confirm this by biopsies or antigen sensitization assays in the present work. Another group suggested, after collecting data from 3877 subjects, that the evidence did not support a direct physiological impact of VDT work on the skin, but rather than any effects were due to psychological stimuli (Liden and Berg 1991).…”
Section: Conclusion and Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…A reasonable explanation for the lower wrinkling and spots would be a small but long-term difference in sun exposure, which may not have been accurately assessed by the survey used in this study. One study reported that Langerhans' cells were depleted in "screen dermatitis" (Gangi and Johansson 1997), but we did not confirm this by biopsies or antigen sensitization assays in the present work. Another group suggested, after collecting data from 3877 subjects, that the evidence did not support a direct physiological impact of VDT work on the skin, but rather than any effects were due to psychological stimuli (Liden and Berg 1991).…”
Section: Conclusion and Discussioncontrasting
confidence: 90%
“…One report stated that "skin disorders" was a category that was more widely reported by VDT operators than similar, non-users of VDTs; however, there was no specific definition given for "skin disorders" (Knave et al 1985). Another study reported dermatologic symptoms such as pain, itch, heat sensation, erythema, papules, and pustules were more commonly reported by users of VDTs (Gangi and Johansson 1997). It has also been suggested that there is a small fraction of the population that is intrinsically more sensitive to EMF, leading to contradictory and confusing epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Gangi and Johansson (1997) detected an increased incidence of skin and CNS alterations among microcomputer's workers. In their study, the workers reported to feel skin -and mucosa -related symptoms, such as pain, itch, heat sensation, erythema, papules, and pustules.…”
Section: Discussionmentioning
confidence: 99%
“…Ekran dermatiti gelişen deride mast hücre sayısında artma, Langerhans hücre sayısında azalma saptanırken, değişiklikler UV hasarı ile benzer bulunmuştur. 22 …”
Section: Ekran Dermati̇ti̇unclassified